Clinical Trial With Secnidazole in a Single Dose in Venezuelan Children Infected by Giardia Intestinalis - Di Prisco, María Cristina; Jiménez, Juan Carlos; Rodríguez, Naima; Costa, Vilma; Villamizar, Jacqueline; Silvera, Alexia; Carrillo, Mónica; Lira, Cleofaf; Zerpa, Edelmira; López, Yesenia (Investigación Clínica, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The aim of this work was to evaluate in an open, non-comparative study the use of secnidazole in oral suspension given to Venezuelan children infected with Giardia intestinalis, from a community in Carapita, a slum area in Caracas. Seventy children from 2 to 11 years old (38 males and 32 females) were treated with a single oral dose of secnidazole (30 mg/Kg of body weight), after clinical and parasitological evaluation to make the diagnosis of active giardiasis. The effectiveness of treatment was determined by clinical examination and parasitological evaluation of feces samples 15 days after treatment. The results showed 95% of clinical cure with a significant decrease of the frequency of gastrointestinal symptoms. The parasitological cure was 98%, there were 4 failures at the end of treatment. Side effects observed after treatment were of mild intensity, lasting only few hours. These results show that a simple dose of secnidazole in an oral suspension is an effective, safe and well tolerated treatment for giardiasis in children and that this drug may be used as a mass treatment in risk populations